Criminalizing Nomadic Femininity: Colonial Trail of the Kathua Rape–Murder. Issue 1 (June 2020) - Sharma, Varun
A reading of Michael Kennedy's (1908) treatise on 'criminal classes' in British India offers fresh perspective on the Kathua rape–murder in historical terms. What emerges through an exercise that connects past to present, colony to nation, is how the pending fate of a Bakarwal girl was first inscribed in colonial ink for being a nomad, and later fulfilled in Independent India for being a Muslim. The manner in which the colonial programme of stigmatizing nomadic societies, particularly its women and children, is being adapted, intensified and given renewed direction through Hindu hyper-nationalism is thus underscored. The failure of civil society to recognize the refraction of colonial power in a communal atmosphere, and thus come up with promising alternatives to prevent such crimes, is further highlighted.